2010
DOI: 10.1038/nn.2690
|View full text |Cite
|
Sign up to set email alerts
|

The same synaptic vesicles drive active and spontaneous release

Abstract: Synaptic vesicles release neurotransmitter both actively (upon stimulation) and spontaneously (at rest). It has been long assumed that identical vesicles use both modes of release; however, recent evidence has challenged this view. Using several assays (FM dye imaging, pHluorin imaging and antibody-labeling of synaptotagmin), in neuromuscular preparations from Drosophila, frog and mouse as well as rat cultured neurons, we suggest that the same vesicles participate in active and spontaneous release.1 Synaptic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
109
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(115 citation statements)
references
References 14 publications
3
109
1
Order By: Relevance
“…To bypass some of the inherent technical problems of using these dyes, we previously used the biosyn technique to permanently label vesicle pools and demonstrated that spontaneous and evoked release derive from separate pools (Fredj and Burrone, 2009), but this view has recently been challenged (Hua et al, 2010;Wilhelm et al, 2010). However, technical issues with the techniques used suggest that there may be inherent problems with the methods of studying vesicle cycling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To bypass some of the inherent technical problems of using these dyes, we previously used the biosyn technique to permanently label vesicle pools and demonstrated that spontaneous and evoked release derive from separate pools (Fredj and Burrone, 2009), but this view has recently been challenged (Hua et al, 2010;Wilhelm et al, 2010). However, technical issues with the techniques used suggest that there may be inherent problems with the methods of studying vesicle cycling.…”
Section: Discussionmentioning
confidence: 99%
“…In one paper (Wilhelm et al, 2010), most of the experiments use FM dyes, with issues that have been discussed previously (Fredj and Burrone, 2009). In a key experiment, Wilhelm et al (2010) use the pH-sensitive exocytosis reporter, synaptopHluorin, to demonstrate similar levels of exocytosis due to both active and spontaneous cycling following labeling of the activitydependent pool.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically in such experiments, both staining and destaining are triggered by extensively stimulating the neurons (evoked activity). Recently, however, synaptic vesicle recycling in response to weak stimulation has also been analyzed, as has recycling in the absence of an external stimulus (spontaneous and miniature synaptic activity) 9,[17][18][19] . Spontaneous and miniature synaptic activities are defined as those that occur in the absence of external stimuli, with the former involving the spontaneous firing of action potentials (Figure 3).…”
Section: Introductionmentioning
confidence: 99%